2014
DOI: 10.1038/nrneph.2014.87
|View full text |Cite
|
Sign up to set email alerts
|

Lipid biology of the podocyte—new perspectives offer new opportunities

Abstract: In the past 15 years, major advances have been made in understanding the role of lipids in podocyte biology. First, susceptibility to focal segmental glomerulosclerosis (FSGS) and glomerular disease is associated with an APOL1 sequence variant, is expressed in podocytes and encodes apolipoprotein L1, an important component of HDL. Second, acid sphingomyelinase-like phosphodiesterase 3b encoded by SMPDL3b has a role in the conversion of sphingomyelin to ceramide and its levels are reduced in renal biopsy sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
90
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(96 citation statements)
references
References 137 publications
(159 reference statements)
5
90
1
Order By: Relevance
“…Cholesterol overload from its elevated carriers i.e . circulating LDLs, as was shown in the present study, might negatively influence the binding of podocyte SD proteins to each other, as which is assembled in lipid rafts and is playing a critical role in the formation of glomerular filtration barrier and maintenance of the interdigitating foot process pattern 42, 46, 47. We found in vivo and in vitro , SD proteins podocin and NEPH1 were dramatically decreased during the challenge of hypercholesterolaemia or ox‐LDL treatment.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Cholesterol overload from its elevated carriers i.e . circulating LDLs, as was shown in the present study, might negatively influence the binding of podocyte SD proteins to each other, as which is assembled in lipid rafts and is playing a critical role in the formation of glomerular filtration barrier and maintenance of the interdigitating foot process pattern 42, 46, 47. We found in vivo and in vitro , SD proteins podocin and NEPH1 were dramatically decreased during the challenge of hypercholesterolaemia or ox‐LDL treatment.…”
Section: Discussionsupporting
confidence: 74%
“…Clinical and experimental studies have provided insights into the roles of lipids and lipid‐modulating proteins as key determinants of podocyte function in health and kidney diseases 42. Joles et al .…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other members of the APOL family, APOL1 possesses a signal peptide that allows for APOL1 to be exported out of the cell and into the bloodstream, where it associates with HDL particles. APOL1 is also believed to play a role in programmed cell death and autophagy (32,33). Recently, Nichols et al (34) showed that the expression of APOL1 in podocytes and endothelial cells is induced by IFNs and Toll-like receptor agonists, suggesting a role for inflammation as a CKD inducer.…”
Section: Discussionmentioning
confidence: 99%
“…In Fabry disease, when the a v b 3 becomes activated, it triggers podocytic contraction and migration, finally contributing to podocyte detachment from the glomerulus and podocyturia. 19,20 Noteworthy, Utsumi et al have found elevated levels of a v b 3 integrin in the urine of individuals with Fabry disease, probably due to the accumulation of Gl3. The augmented localization of the b 3 component was seen mainly in podocytes and in epithelial cells of Bowman capsule.…”
Section: Podocyte Massmentioning
confidence: 99%